Correlation between Baseline Plasminogen Activator Inhibitor Levels and Clinical Outcome during Therapy with Tissue Plasminogen Activator for Acute Myocardial Infarction - Sane, David C; Stump, David C; Topol, Eric J; Sigmon, Kristina N; Kereiakes, Dean J; George, Barry S; Mantell, Susan J; Macy, Elizabeth; Collen, Désiré; Califf, Robert M (Thrombosis and Haemostasis, 1991)
Baseline plasminogen activator inhibitor (PAI) levels were examined for their influence on the responses to thrombolysis with recombinant tissue plasminogen activator (rt-PA) administered for acute myocardial infarction during the Thrombolysis and Myocardial Infarction (TAMI)-I study. Baseline PAI activity was 19 ± 21 IU/ml (normal <5 IU/ml) and baseline PAI-1 antigen 54 ± 53 ng/ml (normal 27 ± 16 ng/ml), confirming previous findings of elevated PAI levels during acute myocardial infarction. Among clinical outcomes, lower PAI-1 antigen levels correlated weakly with greater patency at the 90 min angiogram. Thus, high baseline plasma PAI-1 levels may be detrimental to reperfusion with t-PA. There was no correlation with other major in-hospital clinical outcomes including reocclusion at the 7-10 day angiogram, survival to discharge, or bleeding. During the follow up period of 2.0 ± 0.4 years, no relationship between baseline PAI levels and post-discharge reinfarction was observed.